PEMISAHAN, INISIASI, DAN KEMBALI DALAM NOVEL “THE PRISONER OF ZENDA” KARYA ANTHONY HOPE - Hrp, Zainul Syaidin Azri; Satria, Robby (Universitas Putera Batam, 2024)
Abstract This research aims to identify the phases of the hero patterns in “The Prisoner of Zenda” a novel written by Anthony Hope experienced by the main character as the hero. Campbell (2004) mentioned that the pattern is prominent in heroic fiction referred to as monomyth. This research uses a descriptive qualitative design to examine the intricacies of the analysis method by Ratna (2004) the method of library research was employed to gather the data, and the method of descriptive analysis by Ratna (2004) was used to analyze the data. This research was made to fulfill phases of hero patterns Separation, Initiation, and Return. The result of the research Rudolf Rassendyll as the hero has passed 15 stages of hero's patterns based on Campbell's theory only Woman as a temptress and The Magic Flight no found in The Prisoners of Zenda. The stages of the hero's patterns have the function of uncovering the quest that the hero wants to reach. This leads to the conclusion that hero’s patterns often follow the same pattern as theorized and mentioned in the theory of Joseph Campbell. Keywords: Heroism, Hero Patterns, Separation, Initiation, Return, Preliminary Analysis